Effects of steroidal growth implants alone or in combination with a beta-adrenergic agonist feed additive on the gonadal development of South African Dohne Merino rams and ewes - Webb, E.C. (Edward Cottington) (University of Pretoria, 2022)
Dissertation (MSc Agric: Animal Science (Production Physiology and Product Quality))--University of Pretoria, 2022.